Implementation of Supervision About Patient Safety with an Inguinal Hernia Diagnosed in an Inpatient Room: A Case Study - Tri Afandi, Alfid; Indri Safitri, Resti; Wijaya, Dodi; Fariasih, Cucik (Universitas Bondowoso, 2023)
Introduction: Patient safety has become a global issue that is currently being discussed in all countries. Concerns about patient safety have increased significantly over the last decade. The implementation of supervision is very important in order to improve the implementation of patient safety goals. The purpose of this research is to analyze the implementation of supervision regarding patient safety in patients with a diagnosis of Inguinal Hernia in the Inpatient Room. Method: Used a survey method with a supervision questionnaire for patient safety and a supervision effectiveness questionnaire for patient safety. Results: The results showed that supervision of patient safety in patients with a diagnosis of Inguinal Hernia has been carried out in the Hospital Inpatient Room. Implementation of this supervision is effective to do in order to increase the motivation of nurses in implementing patient safety goals. But the implementation of supervision about patient safety is still not optimally implemented because there are several obstacles such as the patient safety program has not become a priority agenda, there is no driving force, it is carried out under forced conditions such as only because of demands from superiors, there are obstacles due to a lack of understanding of the implementation of patient safety programs, there is no sense of awareness in towards patient safety culture, and non-optimal incident reporting. Conclusion: These results can be a reference for hospitals about the attitude of nurses in monitoring patient safety and should improve existing nursing training by allowing nurses to continue their education to a higher level, by holding regular training on patient safety practices.